Eksistensi Wakil Kelompok Dalam Gugatan Class Action di Indonesia - Ginting, Jamin (Pelita Harapan University, 2003)
Supreme Court Regulation (Penna) No. 1 Year 2002 about class action procedure had Â settled the mean of representative of class as a legal standing in class action procedure. Â Definition of representative of class is one person or more that has or have the same fact, law problem and the same sue with all member of the group. The definition above means that ORNOP/LSM (independent organization non government) can not be a representative of class in the class action sue but have right to sue only by the law. The government as a representative of class action sue just for the public interest, even though the governemt is not a member or part of the group.Â